Education revolutionary ideas for Vietnam students today - Nguyễn Công Đức (Tạp chí Nghiên cứu Khoa học Công đoàn, 2024)
In the current trend of international economic integration, young people and students are the successor force, bringing into play the country’s intellectual resources, the main resource for developing the knowledge-based economy, science and technology, contributing to the development of the knowledge-based economy. a key role is a great force in preserving and building socialism in our country today. In order to deserve to be the "future owner" of the country that is both "pink" and "specialized" in addition to improving professional capacity, young people and students also need to pay attention to the education of revolutionary ideals. Cultivate moral qualities and lifestyle. Within the scope of this article, the author goes to research and learn about revolutionary ideal education; Ho Chi Minh’s thought on revolutionary ideal education and solutions to students’ revolutionary ideals in the current period.